Immunodeficiency, Centromeric Region Instability, Facial Anomalies Syndrome 1 - Kalyani Srinivas; Prajnya Ranganath; Palle Sreelekha; Kalivela Santhimayee; Shaik Mahin (Pediatric Infectious Disease)
The immunodeficiency, centromeric region instability, facial anomalies (ICF) syndrome is a rare autosomal recessive disease characterized by facial dysmorphism, immunoglobulin deficiency, and centromeric instability. We describe a 14-month-old female child with recurrent infections, facial anomalies, and psychomotor retardation. The child had recurrent admissions for fever, cough, and cold—7 times and required intensive care unit (ICU) stay for pneumonia twice at 4 and 9 months of age, urinary tract infection at 4 months of age, febrile seizures at 9 months of age, and left otitis media at 13 months of age. Serum immunoglobulin G (IgG), IgA, and IgM deficiency levels were low. Further evaluation for immunodeficiency revealed a homozygous variant in the deoxyribonucleic acid methyltransferase 3B (DNMT3B) gene at exon 22 c.2401T>C variant.